PERAN GURU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA PADA PELAJARAN SENI BUDAYA KELAS VB DI SD NEGERI PONDOK JAGUNG 01 - Siti Sara Rasyuqa; Muhammad Soleh Hapudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The success of learning cannot be separated from the role of a teacher. Learning motivation needs to be provided as a positive encouragement that helps students achieve learning goals. The low learning motivation of VB class students in Arts and Culture lessons can affect students' personal and social development. This research aims to describe and analyze the role of teachers in increasing students' learning motivation in Arts and Culture lessons in class VB at SD Negeri Pondok Jagung 01. This research method is descriptive qualitative. The techniques used by researchers are observation, interviews and documentation. The data analysis technique uses data triangulation, namely data reduction, data presentation and drawing conclusions. The results of this research are that the role of teachers in increasing students' learning motivation in the Arts and Culture subject class VB at Pondok Jagung 01 State Elementary School has been implemented well, including 1) Teachers as motivators, 2) Teachers as facilitators and 3) Teachers as learning managers. The motivation given is in the form of praise, providing learning facilities according to student needs and classroom management that supports student creativity physically in the classroom and in the learning process. The class teacher's strategy is to give rewards, create cooperation and design fun learning.